2015
DOI: 10.7150/ijms.10263
|View full text |Cite
|
Sign up to set email alerts
|

Combination Analysis in Genetic Polymorphisms of Drug-Metabolizing Enzymes CYP1A2, CYP2C9, CYP2C19, CYP2D6 and CYP3A5 in the Japanese Population

Abstract: The Cytochrome P450 is the major enzyme involved in drug metabolism. CYP enzymes are responsible for the metabolism of most clinically used drugs. Individual variability in CYP activity is one important factor that contributes to drug therapy failure. We have developed a new straightforward TaqMan PCR genotyping assay to investigate the prevalence of the most common allelic variants of polymorphic CYP enzymes CYP1A2, CYP2C9, CYP2C19, CYP2D6 and CYP3A5 in the Japanese population. Moreover, we focused on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
(48 reference statements)
4
38
0
Order By: Relevance
“…Ota et al investigated the prevalence of the most common allelic variants of polymorphic CYP enzymes. They indicated that for CYP1A2, 5%, 37% and 58% of Japanese population were poor, intermediate and extensive metabolizers, respectively . These results are comparable to the CYP1A2 genotype frequencies reported in Caucasians, indicating 10%, 44% and 46% are poor, intermediate and extensive metabolizers, respectively .…”
Section: Discussionmentioning
confidence: 59%
“…Ota et al investigated the prevalence of the most common allelic variants of polymorphic CYP enzymes. They indicated that for CYP1A2, 5%, 37% and 58% of Japanese population were poor, intermediate and extensive metabolizers, respectively . These results are comparable to the CYP1A2 genotype frequencies reported in Caucasians, indicating 10%, 44% and 46% are poor, intermediate and extensive metabolizers, respectively .…”
Section: Discussionmentioning
confidence: 59%
“…Two hundred and eleven studies not fulfilling the eligibility criteria were further excluded. Finally, a total of 86 studies were included in this review. These included 25, 24, 20 and 17 studies on CYP2C9 , CYP2C19 , CYP2D6 and CYP3A5 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding proteins involved in drug metabolism have been associated with more than one ADR, including the P450 genes ( CYP34A (58), CYP2C9 (59)), myeloperoxidase (60), and the glutamate-cysteine ligase catalytic subunit gene GCLC (61). For DILI, polymorphic variants of genes involved in the mitochondrial anti-defense pathway, such as Nrf-2 , may play particularly informative roles (62).…”
Section: Susceptibility Genes Shared Between Drug Hypersensitivity Rementioning
confidence: 99%